Regident Unit Optimization in Motor Vehicle Mutation Services to Improve the Quality of Public Services in the Jurisdiction of Police Region in Boyolali (Indonesian Journal of Police Studies, 2024)
The National Police as a state institution has to serve the community. With the exisctence of public guidance regarding public services which are increasingly critical of the public services provided including services by the Regident Unit in this case motor vehicle mutation services to provide the community’s need for the services provided, it is necessary to improve the quality of public services by the National Police, namely through optimizing the Regident Unit in motor vehicle transfer services. In this thesis the problems include how to manage kind of activities of the Boyolali Police Regident Unit and how to organize resources are in carrying out motorized vehicle transfer services in the jurisdiction of the Boyolali Police. As an analytical tool the author uses management theory, elements of management, the concept of optimization, the concept of Unit Regident Ranmor, and the concepts of public service. This thesis uses a qualitative approach, the type of writing is field research while the data collection techniques are through interviews, observation, and document studies. For the data analysis techniques the authors used data reduction, data presentation, and conclusion. In this thesis it is concluded that the implementation of motorized mutation vehicle services by the Regident Unit is still not optimal referring to the concepts and based on the used theories.
Keywords: Kata Kunci: Optimalisasi, Regident, Pelayanan publik, mutasi kendaraan bermotor.; Keyword: Optimization, Regident, Public Services, Vehicle Mutation Service